2014
DOI: 10.15376/biores.10.1.448-456
|View full text |Cite
|
Sign up to set email alerts
|

Oriented Strand Board Production from Water-Treated Date Palm Fronds

Abstract: The objective of this work was to evaluate some of the important physical and mechanical properties of experimental oriented strandboard panels manufactured from four different cultivars of date palm (Phoenix dactylifera) fronds. Currently date fronds are considered as waste and under-utilized. Open burning and landfill are common practices for such resources. Therefore experimental panels were manufactured from strands washed with water to determine the effect of such treatment on panel properties. Bending ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 12 publications
0
20
0
1
Order By: Relevance
“…Thus, it could be concluded that in terms of the MOR parameter, the respective performances of OSBs from Betung and Andong were superior to those of the OSB from Ampel. Furthermore, the dry-state MOR values with 4% and 5% were superior compared to OSB from palm strand (Hegazy et al 2015). The mean values of wet-state MOR parallel and perpendicular to the surface grain ranged from 9 to 51 N/mm 2 and 11 to 32 N/mm 2 , respectively (Fig.…”
Section: Mechanical Properties Of Osbmentioning
confidence: 88%
“…Thus, it could be concluded that in terms of the MOR parameter, the respective performances of OSBs from Betung and Andong were superior to those of the OSB from Ampel. Furthermore, the dry-state MOR values with 4% and 5% were superior compared to OSB from palm strand (Hegazy et al 2015). The mean values of wet-state MOR parallel and perpendicular to the surface grain ranged from 9 to 51 N/mm 2 and 11 to 32 N/mm 2 , respectively (Fig.…”
Section: Mechanical Properties Of Osbmentioning
confidence: 88%
“…In our experiment, only the two class categories of D and E were used as they considered particleboard particles, which would be mentioned later in the text as coarse particles (class D) and fine particles (class E). Classes A, B, and C were considered as flakes and were used in another study for manufacturing oriented strand board [11].…”
Section: Frond Materialsmentioning
confidence: 99%
“…Date palm fronds, having rich fiber content, were investigated to be used as raw material for experimental particleboard manufacture in several past works [8][9][10][11]. The four investigations above revealed that particleboard panels made from date palm fronds resulted in satisfactory mechanical and physical characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Particleboards have been generated using various species of palm trees as the main material such as date palm (Nemli et al 2001;Hegazy and Aref 2010;Amirou et al 2013;Saadaoui et al 2013;Hegazy et al 2015), Washingtonia palm (García-Ortuño et al 2013), and oil palm (Laemsak and Okuma 2000;Hashim et al 2011a;Rasat et al 2011;Suhaly et al 2012;Wad Nadhari et al 2013;Jumhuri et al 2014;Henao et al 2014;Tajuddin et al 2016). The behavior of the particleboard depends on the species of palm tree and the origin of the particles from the trunk or the leaf.…”
Section: Introductionmentioning
confidence: 99%